2018
DOI: 10.1177/1076029618786574
|View full text |Cite
|
Sign up to set email alerts
|

Low Vitamin D Levels Are Associated With the Development of Deep Venous Thromboembolic Events in Patients With Ischemic Stroke

Abstract: The objective is to determine whether a low serum 25-hydroxyvitamin D (25(OH)D) level is associated with an increased incidence of deep venous thromboembolic events in patients with ischemic stroke. One hundred eighty persons admitted consecutively for inpatient rehabilitation at the Department of Rehabilitation of the First Affiliated Hospital of Wenzhou Medical University with a diagnosis of ischemic stroke from January 2015 to December 2015 were enrolled. The following demographic data were collected: age, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 39 publications
1
50
0
Order By: Relevance
“…Other studies have suggested that 1,25 (OH) 2 D can downregulate proinflammatory signaling and promote inhibition of tissue factor activity, thus reducing a prothrombotic milieu (125). In addition, a limited number of clinical reports, antedating the COVID-19 era suggest a link between the development of vitamin D deficiency and incident thrombotic events, including deep venous thrombosis and cerebrovascular events (126,127,128). This may be especially true in patients who are critically ill and require intensive care, among whom low 25-OHD levels have been reported in up to 80% in the pre-COVID-19 era (129,130).…”
Section: Vitamin D and The Cardiovascular System In Covid-19mentioning
confidence: 99%
“…Other studies have suggested that 1,25 (OH) 2 D can downregulate proinflammatory signaling and promote inhibition of tissue factor activity, thus reducing a prothrombotic milieu (125). In addition, a limited number of clinical reports, antedating the COVID-19 era suggest a link between the development of vitamin D deficiency and incident thrombotic events, including deep venous thrombosis and cerebrovascular events (126,127,128). This may be especially true in patients who are critically ill and require intensive care, among whom low 25-OHD levels have been reported in up to 80% in the pre-COVID-19 era (129,130).…”
Section: Vitamin D and The Cardiovascular System In Covid-19mentioning
confidence: 99%
“…This was accompanied by the up-regulation of TF signaling mediator protease-activated receptor 2 (PAR-2) [70]. Observational data in humans revealed an association between low levels of 25OHD and the development of deep venous thromboembolic (DVT) [71] events in patients with ischemic stroke. Conversely, a significant positive association was found between serum levels 25OHD (> 20 ng/mL) and TF pathway inhibitor (TFPI) [a dual inhibitor of coagulation by binding to both TF/Factor VIIa complex as well as Factor Xa] [72].Most intervention studies however did not show clear benefits of vitamin D supplementation on major cardiovascular events, although most study subjects were not severely vitamin D deficient at baseline [3].…”
Section: Coagulation and Thrombosismentioning
confidence: 99%
“…While the anti-thrombogenic components are antithrombin, plasminogen, tissue plasminogen activator, heparin, thrombomodulin, and protein C and S [53]. The anti-thrombotic effects of vitamin D on these thrombogenic and anti-thrombogenic components of the coagulation system have been very well documented [51,54,55]. A recent study demonstrated the association of low vitamin D levels with the development of deep venous thromboembolic (DVT) events in patients with ischemic stroke [51].…”
Section: Role Of Vitamin D In the Coagulation Pathwaymentioning
confidence: 99%
“…The anti-thrombotic effects of vitamin D on these thrombogenic and anti-thrombogenic components of the coagulation system have been very well documented [51,54,55]. A recent study demonstrated the association of low vitamin D levels with the development of deep venous thromboembolic (DVT) events in patients with ischemic stroke [51]. Likewise, a case-control study observed that the concentration of 25(OH)D was significantly lower in 82 participants with idiopathic lower-extremity DVT as compared to 85 sex and age-matched healthy participants [50].…”
Section: Role Of Vitamin D In the Coagulation Pathwaymentioning
confidence: 99%
See 1 more Smart Citation